Development of a standardized ovine aortic stenosis model: a pathomimetic platform for TAVI evaluation and durability testing - Zhu, Yan; Qin, Nana; Hou, Jie; Li, Baoyin; Liu, Fangxu; Jiang, Xin; Chen, Zhuo; Lin, Xiongtao; Tong, Xiaohang; Wei, Xufeng; Li, Dejian; Hu, Mengsi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTranscatheter aortic valve implantation (TAVI) has gained widespread clinical acceptance owing to its minimally invasive approach and enhanced postoperative recovery. This study developed a standardized ovine aortic stenosis (AS) model through surgical implantation of a circular bioengineered annular stent in the aortic root, creating a reproducible pathomimetic platform for TAVI evaluation. Following hemodynamic stabilization, TAVI procedures were performed to systematically assess mid-to-long-term valve functionality and calcification progression.MethodsAS model was established in 11 sheep using extracorporeal circulation assistance technology. Following hemodynamic stabilization (2–4 weeks), TAVI was performed. The modeled sheep were divided into two groups to monitor valve conditions at 3 months (n = 6) and 6 months (n = 5), respectively. Additionally, a non-modeled control group was established, with valve conditions assessed at 3 months (n = 2) and 6 months (n = 1). Preoperative ultrasound data, collected on the day of TAVI, which served as the baseline. Key hemodynamic parameters including blood flow velocity, transvalvular pressure gradient, and left ventricular ejection fraction were measured at 30, 90, and 180 days postoperatively, in accordance with Valve Academic Research Consortium-3 (VARC-3), to evaluate temporal changes in hemodynamics. The effects of the AS model on valve function were further analyzed by integrating final histopathological findings and calcification degree outcomes.ResultsSuccessful AS model establishment was achieved in all 11 sheep, with significant increases in mean transvalvular pressure gradient (Δ+17.98 ± 12.71 mmHg) and peak flow velocity observed post-modeling (Δ+ 2.23 ± 0.38 m/s). Post-TAVI evaluation demonstrated progressive hemodynamic normalization, achieving pre-modeling levels (1.72 vs. 6.91 mmHg, P = 0.058/0.80 vs. 1.51 m/s, P = 0.065) at 180-day follow-up. LVEF remained stable throughout the experimental period. Histopathological analysis indicated comparable calcification burden between 90 and 180 days (Calcium Content: P = 0.7459 and Calcification Score: P = 0.5455).ConclusionsThe surgically induced ovine AS model effectively replicates clinically relevant hemodynamic perturbations while maintaining excellent procedural feasibility. TAVI in this model achieves complete hemodynamic normalization without accelerating bioprosthetic valve degeneration or calcification. This standardized preclinical platform enables rigorous evaluation of TAVI device performance and durability, providing robust scientific validation for translational applications.